Kaji Numerik Pengaruh Beban Dinamik Terhadap Tekanan Dan Ketebalan Lapisan Film Pada Cylindrical Roller Bearing Menggunakan Metode Beda Hingga - Putra, Afriadham; Cupu, Dedi Rosa Putra; Nazaruddin, Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Roller bearings are one type of bearing (cylindrical) that uses a roll or cylindrical shape as a friction damper on the bearing. The biggest factor influencing the performance of roller bearings is the dynamic load. One source of dynamic load on a bearing is vibration. This study examines how the influence of dynamic loads on the thickness of the film layer formed and the pressure that occurs in contact between the cylindrical roller and the inner ring. The dynamic load studied in this study is the fluctuation of the load generated by external influence of vibration, which theoretically changes the actual load acting on the sinusoidal fluctuating bearings. The simulation begins with a static load condition, the results of this static simulation are used for dynamic load simulation in solving the Reynolds transient equation where the influence of time cannot be ignored anymore. The finite difference method with a central-difference scheme is used to solve the Reynolds equation. The results showed the thickness of the film layer and the pressure that occurs changes every time. The greater the amplitude of the excitation the greater the pressure applied to the contact, the thinner the film formed. The frequency of excitation affects the number of repetitions of loads that work at one particular time. Keywords: Transient Elastohydrodynamic Lubrication, Roller Bearings, Dynamic Loads, Amplitude, Frecuency